The Degree of Effectiveness of the New Teachers Program in Enabling Science Teachers to Possess Total Quality Standards in Public Schools in Ajloun Governorate from the Point of View of Principals - Abdalgani, Muwaffag Okleh Mohammad (Journal of Educational and Psychological Sciences, 2022)
This Study aimed to identify the degree of effectiveness of the new teacher's program in enabling science teachers to possess total quality standards in public schools in Ajloun governorate from the point of view of principals. To achieve the objectives of the study, the researcher used the descriptive analytical method, and a questionnaire consisting of (39) items divided into five areas, which were distributed to a random sample consisting of (90) principals. with a total average (3.66 out of 5), with (medium) effectiveness and at the level of the domains; The field of lesson implementation got the highest average (3.79), then evaluation with an average of (3.68), thirdly, developing students’ thinking with an average of (3.68), all with a degree (high), and fourthly planning with an average of (3.64), and finally employing educational technology with an average of (3.51) and a (medium) degree. The results showed that there were no statistically significant differences at the level (α ≤ 0.05) between the managers' perspectives, refer to the sex variable, while there were differences refer to the variable of experience and in favor of experience (10 years or more). Based on the results, the researcher recommended enabling teachers to possess comprehensive quality standards, and strengthening the partnership between the Ministry of Education and teacher training colleges. He also suggested conducting more studies on the subject.
Keywords: Degree of Effectiveness; New Teachers Program; Total Quality Standards; Ajloun Directorate